The Impact of Fintech on Bank Cost Efficiency - Babaei, Yasamin (2025)
A Master of Science thesis in Finance (MSF) by Yasamin Babaei entitled, “The Impact of Fintech on Bank Cost Efficiency”, submitted in May 2025. Thesis advisor is Dr. Ali Mirzaei. Soft copy is available (Thesis, Approval Signatures, Completion Certificate, and AUS Archives Consent Form).